2020
DOI: 10.1177/0961203320974081
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and risk of sexual dysfunction: A systematic review and Meta-Analysis

Abstract: Objective To systematically review and summarize the available literature regarding the association between systemic lupus erythematosus (SLE) and sexual dysfunction (SD) in both sexes. Methods We retrieved relevant studies from the following databases: PubMed, Embase, Cochrane Library, and Web of Science. Two reviewers independently reviewed the studies in our sample, assessed their validity, and extracted relevant data. Sensitivity and subgroup analyses were performed to distinguish sources of heterogeneity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
0
5
1
Order By: Relevance
“…Our study mainly evaluated the effects of life status and depression in both the SLE and control groups. The results indicated that the prevalence of female sexual dysfunction between the two groups did not exhibit a significant difference, which was not reported in previous meta-analyses [8,9].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Our study mainly evaluated the effects of life status and depression in both the SLE and control groups. The results indicated that the prevalence of female sexual dysfunction between the two groups did not exhibit a significant difference, which was not reported in previous meta-analyses [8,9].…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding SLE, studies have reported that the factors affecting patients' sexual function may be caused by the disease itself, mental health disorders (e.g., depression and anxiety), and drug treatment [6,7]. Previous metaanalyses have revealed that SLE has potential adverse effects on the sexual function in women with SLE; however, no further analysis of specific performance and treatment has been conducted [8,9].…”
Section: Introductionmentioning
confidence: 99%
“… 4 A meta-analysis of 8 studies involving 758 patients in the SLE group and 1724 individuals in the control group showed that SLE was significantly associated with an increased risk of sexual dysfunction. 5 However, a few studies have explored the association of demographic data and clinical manifestations with intimacy in patients with SLE, especially in Asian populations. 4 6 We hypothesised that demographic factors, clinical manifestations and disease activity of SLE would affect the intimate relationships in female patients with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular disease was found to be a significant and independent risk factor for impaired sexual function 4. A meta-analysis of 8 studies involving 758 patients in the SLE group and 1724 individuals in the control group showed that SLE was significantly associated with an increased risk of sexual dysfunction 5. However, a few studies have explored the association of demographic data and clinical manifestations with intimacy in patients with SLE, especially in Asian populations 4 6.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis [8] revealed the rate of sexual dysfunction (SD) in SLE patients, ranging from 15% to 85.9%, which indicated the severity of the poor assessment and management of these issues. Over the past several years, only a handful of studies [9][10][11][12] used a validated tool of the Female Sexual Function Index (FSFI) to explore the relationship between SLE and sexual problems, demonstrating that SLE was associated with an increased risk of female sexual problems.…”
Section: Introductionmentioning
confidence: 99%